The Influence of Importance in Self-Report of Quality of Life in Chilean Young People - Urzúa, Alfonso; Universidad Católica del Norte. Antofagasta, Chile. (2015)
While self-report of overall quality of life has been widely examined, there are no studies that explore the impact of the relative importance people give to the various categories of their quality of life. Therefore, with a quantitative methodology and a co-relational transverse design, we analyze differences in the assessment when the importance given to each category is evaluated. Participants were 530 students from the city of Antofagasta in the North of Chile, aged between 15 and 18 years. They were from subsidized, public secondary schools and private and state universities in the city who were assessed using the KIDSCREEN-27 questionnaire. Results: Differences were found in the assessment of categories when results were analyzed based on gender and age and when incorporating an assessment of importance. Even when the results were not conclusive, there was evidence of a need to incorporate an importance variable when assessing quality of life.